Pengaruh Conversation Dan Co-Creation Terhadap Customer Loyalty Dengan Mediasi Experience Quality Dan Moderasi Currency Pada Pengguna Layanan Vod Vidio Di Kabupaten Bekasi - Riana Ezra Savitry Is Handiani; Surya Bintarti (Journal of Economic, Bussines and Accounting (COSTING), 2024)
Since the Covid-19 pandemic arrived in Indonesia, all people have become accustomed to carrying out their activities from inside the house, one of which is watching films. Vidio is an online streaming service platform that provides various online videos such as films, sports broadcasts, original series and many more. The aim of this research is to test the effect customer loyalty to conversation, co-creation, currency and experience quality on the Vidio VoD application service. This research was conducted within the boundaries of the Bekasi Regency community area with a total of 114 respondents, namely users who have used Vidio. The sampling technique used isNonprobability sampling namely by method purposive sampling. This research tests correlation and regression with the help ofsoftware SmartPLS 3.0 is used to test validity and reliability. This research shows that: 1) Activities Conversation carried out by the serviceVideo on Demand Vidio is able to push the level Experience Quality consumer; 2) Co-Creation which is set by the serviceVideo on Demand Vidio is able to push the level Experience Quality consumer; 3) Activities Conversation What is done is able to moderate Currency on serviceVideo on Demand Vidio against the level Experience Quality consumer; 4) Co-Creation determined can moderate Currency on Vidio's Video on Demand service Experience Quality consumer; 5) Experience Quality what consumers feel about the service Video on Demand Vidio is able to push the level Customer Loyalty; 6) Activities Conversation that can be done to mediate Experience Quality on service Video on Demand Vidio against Customer Loyalty; 7) Co-Creation determined to be able to mediate Experience Quality on service Video on Demand Vidio against the level Customer Loyalty.